31.0k views
2 votes
27
Solve for x.
5x – 5 = 9x + 3
X =

User Anshumans
by
6.0k points

2 Answers

3 votes

Answer:


x=-2

Explanation:

Step-by-step on how to solve it is in the picture below ↓

Hope this helps! :)

27 Solve for x. 5x – 5 = 9x + 3 X =-example-1
User Oleg Shleif
by
5.6k points
3 votes

Answer:

- 2

Explanation:

Add 5 From Both Sides

Simplify

Subtract 9x from both sides of the equation

Simplify

Divide both sides of the equation by the same term

Simplify

Solution

User Andrea Golin
by
4.8k points